2011
DOI: 10.1111/j.1399-5448.2010.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Young patients with both type 1 diabetes mellitus and asthma have a unique IL-12 and IL-18 secretory pattern

Abstract: Patients with both T1DM and asthma display a different pattern of IL-12 and IL-18 expression compared to patients with one disease only and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Rachmiel et al, for example, investigated in 2011 the IL‐12 and IL‐18 secretion pattern in these two groups, knowing that the two cytokines play an important role in the regulation of both Th1‐ and Th2‐mediated diseases . They found that patients with both T1DM and asthma had higher serum levels of IL‐12 and IL‐18 than controls . Cytokines play an important role in inflammatory processes and therefore also in inducing beta‐cell damage in patients with T1DM .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Rachmiel et al, for example, investigated in 2011 the IL‐12 and IL‐18 secretion pattern in these two groups, knowing that the two cytokines play an important role in the regulation of both Th1‐ and Th2‐mediated diseases . They found that patients with both T1DM and asthma had higher serum levels of IL‐12 and IL‐18 than controls . Cytokines play an important role in inflammatory processes and therefore also in inducing beta‐cell damage in patients with T1DM .…”
Section: Discussionsupporting
confidence: 90%
“…IL-12 and IL-18 than controls (41). Cytokines play an important role in inflammatory processes and therefore also in inducing beta-cell damage in patients with T1DM (15).…”
Section: Discussionmentioning
confidence: 81%
“…Different types of innate immune cells such as T cells, eosinophils, macrophages (M φ ), and dendritic cells (DC) as well as proinflammatory cytokines and chemokines are present during insulitis [ 4 , 9 ]. The relationship between T1DM and high levels of inflammatory cytokines such as interleukin- (IL-) 1 β [ 10 14 ], interferon- (IFN-) γ [ 15 ], tumor necrosis factor- (TNF-) α [ 16 ], IL-12 [ 17 , 18 ], and macrophage migration inhibitory factor (Mif) [ 19 24 ] has been widely recognized.…”
Section: Introductionmentioning
confidence: 99%
“…In our setting, more advanced disease in older recipients may be linked to more inflammation in PLN than young recipients. Pro-inflammatory IL-12, IL-1β, IL-6 and IL-17 cytokines lead to the loss of Treg from T1D patients [ 49 52 ]. More pro-inflammatory cytokines from older vs. young recipients may similarly reduce PLN Treg.…”
Section: Discussionmentioning
confidence: 99%